Bioavailability of lead and cadmium in soils artificially contaminated with smelter fly ash - Komárek, Michael; Ettler, Vojtech; Száková, Jirina; Sebek, Ondrej; Tlustos, Pavel (Bulletin of environmental contamination and toxicology, 2009)
This study evaluated lead and cadmium uptake by maize grown on soils artificially spiked with smelter fly ash and possible changes in chemical fractionation of these metals in the soil. Maize grown on the less contaminated soil (1,466 mg Pb kg(-1); 19 mg Cd kg(-1)) did not exhibit any chlorosis/necrosis symptoms or lower biomass yields compared to the control. The addition of the chelating agent ethylenediaminetetraacetic acid increased lead uptake by maize, as expected. Neither maize cultivation nor the addition of the chelant influenced significantly the chemical fractionation of lead and cadmium in the soil during the experiment.
Keywords: Zea mays; pevné částice; olovo; Chemical Fractionation; půda; kukuřice setá; Lead; popel uhelný; Coal Ash; biomasa; látky znečišťující životní prostředí; Particulate Matter; Cadmium; Carbon; Environmental Pollutants; kadmium; Soil; Biomass; uhlík; Metallurgy; hutnictví; chemická frakcionace